Android & Ios Covid19 Data Clustering Application Using Flutter with K-Means Algorithm - Wildan Alfy Syahry; Fauziah; Ratih Titi Kumalasari (Institute of Computer Science (IOCS), 2020)
In the current pandemic, Covid19 has a tremendous impact on the survival of mankind. The government has made efforts to spread Covid19 so that it does not spread much in Indonesia, and now it is in the process of being called PSBB (Large-Scale Social Restrictions) but many Indonesians still violate and ignore the program. There are still many who travel to the Mall, Coffe shop, and even abroad. In this 2020 Era, mobile technology is now an important component of human life, so it is possible to harness the power of mobile technology to make the Indonesian people who still want to violate the program of this government aimed at reducing the spread of COVID-19. So the author aims to create an application that can be accessed through Android & Ios